Transseptal Access for Left Atrial Ablation: The Catheter‐Probing Techniques Are Not Without Risk. (29th January 2014) - LEHRMANN, HEIKO; SCHNEIDER, JENS; JADIDI, AMIR S.; PARK, CHAN‐IL; SCHIEBELING‐RÖMER, JOCHEN; ALLGEIER, JÜRGEN; ARENTZ, THOMAS; WEBER, REINHOLD
Risk of Catheter‐Probing During Transseptal Access: Background: Transseptal puncture (TP) is a prerequisite for LA ablations. LA access can be gained by catheter probing in case of PFO (trans‐PFO method) or puncture of the interatrial septum (IAS) using a transseptal needle. A 2nd access can again be gained via PFO, a 2nd TP or catheter probing of the previous puncture site (probe‐TS method). This study investigates the risk factors and complications related to the mode of transseptal access. Methods and Results: From August 2010 to August 2012, a total of 544 LA ablations, were performed. The mode of LA access was either a double TP or a single TP followed by the probe‐TS or the trans‐PFO method, respectively. TP was always guided by TEE and was successfully performed without complications in all cases. In contrast, 6/410 patients (1.5%) in whom catheter probing was performed (probe‐TS, n = 4, trans‐PFO, n = 2) had a dissection of the superior IAS originating from inside the oval fossa (n = 5) or perforation above the oval fossa (n = 1). Perforation into the pericardial space occurred in 4/6 patients, leading to one cardiac tamponade. In 5/6 patients, LA ablation was successfully completed, after repeated TP, despite effective anticoagulation. Patients with complications had the following characteristics: LA size 46 ± 4 mm, persistent AF (5/6), a repeat transseptal procedure (3/6) and a right‐sided pouch (RSP, 5/6). Conclusions: Interatrial septum dissection/perforation, occasionally with perforation into the pericardial space, is an unreported complication of TP, especially with the catheter‐probing techniques. An RSP is an unrecognized risk factor in this context and can be visualized by TEE.